Challenges and obstacles implementing evidence-based food fortification policy in a high-income country - Endevelt, Ronit; Tulchinsky, Theodore H.; Stahl, Ziva; Mor, Zohar; Davidovitch, Nadav; Levine, Hagai; Troen, Aron M. (Frontiers in Public Health, 2023)
The World Health Organization (WHO) recognizes food fortification as one of the most cost-effective and beneficial public health measures available. Mass fortification policies and regulations can reduce health disparities, including in high-income countries, by improving micronutrient intake among food-insecure or high-risk populations without changing their diet or behavior. While international health organizations have traditionally prioritized technical assistance and grants to medium and low-income countries, it is important to recognize that micronutrient deficiencies may also pose an important yet underappreciated public health problem in many high-income countries. Nevertheless, some high-income countries, including Israel, have been slow to adopt fortification, due to a variety of scientific, technological, regulatory, and political barriers. Overcoming these barriers requires an exchange of knowledge and expertise among the all stakeholders to achieve cooperation and broad public acceptance within countries. Similarly, sharing the experience of countries where the matter is in play may help inform efforts to advance fortification globally. Here we share a perspective on progress and barriers to achieve this goal in Israel, to inform efforts made to avoid the regrettable waste of unrealized human potential from prevalent yet preventable nutrient deficiency conditions, in Israel and beyond.